Longitudinal variations of laryngeal overpressure and voice‐related quality of life in spasmodic dysphonia. (7th October 2014) - Yeung, Jeffrey C.; Fung, Kevin; Davis, Eric; Rai, Sunita K.; Day, Adam M. B.; Dzioba, Agnieszka; Bornbaum, Catherine; Doyle, Philip C.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Adductor spasmodic dysphonia (AdSD) is a voice disorder characterized by variable symptom severity and voice disability. Those with the disorder experience a wide spectrum of symptom severity over time, resulting in varied degrees of perceived voice disability. This study investigated the longitudinal variability of AdSD, with a focus on auditory–perceptual judgments of a dimension termed laryngeal overpressure (LO) and patient self‐assessments of voice‐related quality of life (V‐RQOL). Study Design Longitudinal, correlational study. Methods Ten adults with AdSD were followed over three time periods. At each, both voice samples and self‐ratings of V‐RQOL were gathered prior to their scheduled Botox injection. Voice recordings subsequently were perceptually evaluated by eight listeners for LO using a visual analog scale. Results LO ratings for all‐voiced and Rainbow Passage sentence stimuli were found to be highly correlated. However, only the LO ratings obtained from judgments of AV stimuli were found to correlate moderately with self‐ratings of voice disability for both the physical functioning and social‐emotional subscores, as well as the total V‐RQOL score. Based on perceptual judgments, LO appears to provide a reliable means of quantifying the severity of voice abnormalities in AdSD. Conclusions Variability in self‐ratings of the V‐RQOL suggest that perceived disability related to AdSD should be actively monitored. Further, auditory–perceptual judgments may provide an accurate index of the potential impact of the disorder on the speaker. Similarly, LO was supported as a simple clinical measure that serves as a reliable index of voice change over time. Level of Evidence 4. Laryngoscope, 125:661–666, 2015